Dipeptidyl Peptidase-4 Inhibitors for the Potential Treatment of Brain Disorders; A Mini-Review With Special Focus on Linagliptin and Stroke - Darsalia, Vladimer; Johansen, Odd Erik; Lietzau, Grazyna; Nyström, Thomas; Klein, Thomas; Patrone, Cesare (Frontiers in Neurology, 2019)
Cerebral stroke is a leading cause of death and persistent disability of elderly in the world. Moreover, after the age of 55, the risk of stroke doubles with each passing decade. Of all strokes, approximately 85 percent are ischemic, caused by blockage of cerebral arteries and remaining hemorrhagic, caused by intracerebral or subarachnoid bleeding. Although stroke prevention by targeting several risk factors such as diabetes, smoking, sedentary lifestyle, hypertension, alcohol abuse and hyperlipidemia have decreased the stroke incidence, the total number of strokes is increasing due to the population aging. After an ischemic stroke, the damage in the ischemic core occurs very quickly and is irreversible. The surrounding penumbra maintains residual blood flow and can be potentially rescued by timely intervention. However, post-stroke acute pharmacological strategies aimed to reduce stroke-induced brain injury have failed in clinical trials despite being effective in animal models. Approximately 70% of surviving stroke patients eventually recover from stroke-induced neurological impairments after rehabilitation in the post-acute phase. However, about 30% do not recover and remain permanently dependent on supportive care in activities of daily living. Therefore, strategies to improve stroke recovery in the post-acute phase are highly needed. Although preclinical studies pharmacologically targeting stroke recovery show promising results, clinically this field is still underdeveloped. In summary, there is a very high medical need for effective stroke therapies that can decrease stroke incidence, reduce acute brain injury and improve post-stroke recovery. Linagliptin is a dipeptidyl peptidase-4 inhibitor which is clinically approved to reduce hyperglycemia in type 2 diabetes. Interestingly, linagliptin has also shown glycaemia-independent beneficial effects in the brain in preclinical studies supported with some clinical data. Although potentially very interesting for the development of new strategies against stroke, the mode of action of linagliptin in the brain is still largely unknown. The purpose of this mini-review is to summarize and discuss the recent experimental and clinical work regarding the effects of linagliptin in the central nervous system, with special emphasis on acute neuroprotection, stroke prevention and post-stroke recovery. We also highlight the main questions in this research field that need to be addressed in clinical perspective.